Interstitial Lung Disease Associated with Collagen Vascular Disease - Antonio Solis Aramayo, Marco; Lopez Lopez, Antonio (Clinical Anti-Inflammatory & Anti-Allergy Drugs (Discontinued), 2014)
Collagen vascular diseases (CVDs), also known as connective tissue disorders (CTDs), include a diverse group of immunologically mediated inflammatory disorders. Systemic inflammatory response may affect many organs. Lung disease—especially interstitial lung disease (ILD)—is frequent in the course of rheumatological diseases and causes mortality and morbidity rates to increase. Since the overall incidence of ILD has been estimated at 15%, physicians are urged to make an early diagnosis and decide the best treatment for ILD in CVDs. There are several tests to improve the accuracy of diagnosis, treatment and prognosis, such as high-resolution computed tomography (HRCT), pulmonary function test, broncho-alveolar lavage (BAL), and surgical lung biopsy. A multi-disciplinary team made up of specialists with extensive expertise in this area must determine when to use each. This document is a review of the diagnosis, treatment and prognosis of ILD in CVDs.
Keywords: collagen vascular disease